Keeping modelling notebooks with TRACE: Good for you and good for environmental research and management support. (February 2021) - Ayllón, Daniel; Railsback, Steven F.; Gallagher, Cara; Augusiak, Jacqueline; Baveco, Hans; Berger, Uta; Charles, Sandrine; Martin, Romina; Focks, Andreas; Galic, Nika; Liu, Chun; van Loon, E. Emiel; et al.
Abstract: The acceptance and usefulness of simulation models are often limited by the efficiency, transparency, reproducibility, and reliability of the modelling process. We address these issues by suggesting that modellers (1) "trace" the iterative modelling process by keeping a modelling notebook corresponding to the laboratory notebooks used by empirical researchers, (2) use a standardized notebook structure and terminology based on the existing TRACE documentation framework, and (3) use their notebooks to compile TRACE documents that supplement publications and reports. These practices have benefits for model developers, users, and stakeholders: improved and efficient model design, analysis, testing, and application; increased model acceptance and reuse; and replicability and reproducibility of the model and the simulation experiments. Using TRACE terminology and structure in modelling notebooks facilitates production of TRACE documents. We explain the rationale of TRACE, provide example TRACE documents, and suggest strategies for keeping "TRACE Modelling Notebooks." Highlights: The quality and reproducibility of modelling would be increased by keeping modelling notebooks. Simulation modellers have not yet developed a strong culture of keeping notebooks. We propose a standard format for notebooks based on the TRACE document framework. We make recommendations about the type of information to be included in the notebooks. We describe existing tools to keep notebooks.